Walter D. Mignolo and Catherine E. Walsh, On Decoloniality: Concepts, Analytics, Praxis (Durham, NC: Duke University Press, 2018). ISBN: 978-0-8223-7177-9 - Burocco, Laura (Kronos: Southern African Histories, 2024)
Background: One of the intended aims of the 'On Decoloniality' series published by Duke University Press, as stated by the editors, Catherine E. Walsh and Walter Mignolo, is to create and illuminate 'pluriversal and interversal paths, that disturb the totality from which the universal and the global are most often perceived'. This does not amount to a rejection of western thought, which is also part of the pluriversal, but a disavowal of the western construction of universality. It stands as a search for a respectful non-competitive coexistence of multiple, reciprocal recognitions among different intellectual traditions and geopolitical struggles from below, emerging from different parts of the world, in addition to South America, Eastern Europe, Asia and the 'south in the north. It requires the deployment of energies and forces towards affirmative, and not merely defensive, actions.